Improving Early Childhood Fine Motor Development Through Weaving Activities - Ilham Kamaruddin; Achmad Abdul Azis; Mohammad Syahru Assabana; Arif ismunandar; Duwi Meilina (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
Early childhood fine motor development can be obtained through supportive learning media. One of them is with paper media. Children can crumple the paper and make patterns on paper with paper media. In this study, the use of writing as a medium is used for weaving activities from articles. In addition to utilizing form as a learning medium, weaving activities are an Indonesian cultural heritage that must be introduced to the next generation early. This research is a class action research, while the object is carried out on 25 RA children in Lampung. The results of this study indicate that most children's motor skills can develop as expected (BSH) through weaving activities with paper in children. Weaving activities can train children's skills in coordinating their eyes and hands, especially finger movements, to stimulate skills in controlling actions involving small or delicate muscles.